Ejecución Presupuestaria de la Federación Provincial Estudiantil de Los Ríos - Julio Macias, Irma Lucia (2018)
One of the components most sensitive to changes within the budgetary process is the execution phase, since it is exposed to various factors that can affect its behavior. This case study will focus on the BUDGETARY EXECUTION OF THE STUDENT SPORTS FEDERATION OF LOS RIOS. The Student Sports Federation of Los Ríos is a non-profit non-governmental society in charge of promoting the good use of free time of the student population; the same that each year receives public financial resources destined for the fulfillment of its objectives to be followed during the year. The main purpose of this work is noted in the correct distribution of the budget and its execution. The budget is an estimate of the use of a certain amount of money during a certain time, therefore budget execution is the process by which this estimate is transformed into a set of actions aimed at the use of human, material and financial resources. in the budget. The present work is framed under the sub-line of research of the Engineering in Accounting and Audit "Financial Management and Social Commitment", resorting to the use of field research that usually implies a union between the method of observation, interviews and analysis to collect data from primary sources.